Representations On Teaching Vocation In Entrants To Pedagogy In Chilean State Universities - Sandoval Rubilar, Pedro Rodrigo; Bustos Gonzalez, Raul Antonio; Maldonado Fuentes, Ana Carolina; Pavie Nova, Alex; Valdes Romano, Grisel Aleny Cincia (My University, 2020)
The paper is part of the study of initial teacher training and seeks to unveil representations, at the level of information and assessment about the teaching profession and its vocational dimension, that have students who enter pedagogy in five state universities, located in the north, center, south and extreme south of Chile, being a sample corresponding to 37.40% of students enrolled in pedagogy of first year in such universities. A comparative study of a descriptive and interpretative type was carried out, with a mixed approach that integrates techniques of a quantitative and qualitative nature, whose purpose is to characterize the students and provide relevant information for the implementation of public policies, as well as for the training institutions.